Clinical-epidemiological study of Bordetella pertussis infection in the Gran Canaria island in the period, 2008-2016 - Laura Iglesias; Antonio Casabella Pernas; Melisa Hernández Febles; Elena Colino Gil; Alicia Eisman Maraver; María José Pena López (Elsevier, 2018)
Objective: Describe the epidemiological and clinical pattern of Bordetella pertussis infection (whooping cough) among hospitalised infants less than one year-old in a paediatric hospital in Gran Canaria. Patients and methods: A retrospective review of the patient hospital records was performed, and recording only those with a microbiological diagnosis of pertussis infection detected using polymerase chain reaction, from January 2008 to December 2016. Results: A total of 110 patients were identified, of which 105 (95.4%) were less than 6 months old, and 59.1% were males. The annual incidence of hospital admissions was estimated between 13.7 and 425.0 cases per 100 000 infants <12 months old, with 2 peaks in 2011 and 2015. Household members were the main potential sources of infection. Main clinical features were pertussis cough associated with signs of catarrh, cyanosis, and lymphocytosis. Complications occurred in 15.4% of the patients (mainly pneumonia), but the outcome was favourable in all the cases. A lower age and non-vaccination were associated with an increased risk of developing complications (p < .05). Viral co-infection occurred in 31.6% of infants diagnosed with pertussis. Conclusions: The incidence of pertussis has increased in the last years in Gran Canaria, with a lower development of complications and mortality rates compared with the previous period. Lower age and non-vaccination status are considered risk factors for developing complications. Vaccination in pregnant women will probably lead to a decline in the incidence in the future, especially in infants younger than 6 months. Resumen: Objetivo: Describir el patrón epidemiológico y clínico de la infección por Bordetella pertussis (tosferina) en niños menores de un año hospitalizados en un hospital pediátrico de Gran Canaria. Pacientes y métodos: Se revisaron retrospectivamente las historias clínicas de los pacientes con diagnóstico microbiológico de infección por B. pertussis mediante reacción en cadena de la polimerasa, de enero de 2008 a diciembre de 2016. Resultados: Se identificaron 110 pacientes, de los cuales 105 (95,4%) fueron menores de 6 meses y el 59,1% eran varones. La incidencia anual de hospitalización se estimó entre 13,7 y 425,0 casos por cada 100.000 lactantes menores de 12 meses, con 2 picos en 2011 y 2015. Los familiares cercanos fueron las principales fuentes de contagio potenciales. Las principales manifestaciones fueron la tos pertusoide asociada con signos catarrales, cianosis y linfocitosis. El 15,4% de los pacientes presentaron complicaciones (principalmente neumonía), pero la evolución fue favorable en todos los casos. La menor edad y la no vacunación se asociaron con un mayor riesgo de desarrollar complicaciones (p < 0,05). La coinfección viral ocurrió en el 31,6% de los pacientes diagnosticados de infección por B. pertussis. Conclusiones: La incidencia de infección por B. pertussis ha aumentado en los últimos años en nuestra área, con un menor desarrollo de complicaciones y con tasas de mortalidad inferiores al período anterior. La menor edad y la no vacunación previa se consideran factores de riesgo para el desarrollo de complicaciones. La vacunación en mujeres embarazadas probablemente disminuirá la incidencia en el futuro, sobre todo en niños menores de 6 meses.